JAKOŚĆ W MEDYCYNIEDepression in chronic heart failure - Szyguła-Jurkiewicz, Bożena; Pudlo, Robert; Samborski, Konrad; Muzyk, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Chronic heart failure (HF) is one of the most challenging problems in cardiology. Depression often coexists with HF. It can develop at any stage of heart disease: as a response to the diagnosis, disease exacerbation or poor prognosis. There is evidence of common pathophysiological pathways in the two diseases: neurohormonal stimulation, arrhythmias, inflammation and blood hypercoagulability. Although the correlation between depression and poor HF prognosis is well recognised, it is still uncertain whether depression treatment can have a positive effect on HF course. It should be noted that tricyclic antidepressants cause orthostatic hypotension, tachycardia and conduction disorders. Most studies confirm the safety of use of selective serotonin reuptake inhibitors (SSRI), bupropion and venlafaxine in HF patients. In conclusion, the detection of depressive symptoms and the efficacy of depression therapy in HF patients is unsatisfactory. This is largely due to the diagnostic difficulties arising from similar clinical manifestations and lack of guidelines in patients suffering from both diseases.